2018
DOI: 10.1016/j.surfcoat.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate bias voltage on defect generation and their influence on corrosion and tribological properties of HIPIMS deposited CrN/NbN coatings

Abstract: Substrate bias voltage is one of the most influential deposition parameter for physical vapour deposition processes as it can directly control the adatom mobility during coating growth. It influences the hardness, roughness as well as the microstructure of the coatings. Thus, bias voltage could also affect the defect formation during the coating deposition. High Power Impulse Magnetron Sputtering (HIPIMS) has been proven useful in producing void free and arc droplet free dense coatings. However, such coatings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
4
14
1
Order By: Relevance
“…To the best of our knowledge, in this work we have shown for the first time that such effects can occur due to the ionic potential. The formation of open pores at the surface has also been reported for relatively harder materials, such as CrN and NbN deposited by HiPIMS [75]. Thus, our findings are of general interest for variety of thin film deposition processes.…”
Section: Temporal Behavioursupporting
confidence: 80%
“…To the best of our knowledge, in this work we have shown for the first time that such effects can occur due to the ionic potential. The formation of open pores at the surface has also been reported for relatively harder materials, such as CrN and NbN deposited by HiPIMS [75]. Thus, our findings are of general interest for variety of thin film deposition processes.…”
Section: Temporal Behavioursupporting
confidence: 80%
“…The curves of corrosion tests and the calculated results, by means of the Tafel Extrapolation Method are shown in Figure 62 and Table 20, respectively. Differently of what was found by Biswas et al (2018b), the coating with more defects presented here the higher corrosion resistance. Of course there are other mechanisms in play.…”
Section: Fourth Stage -Evaluation Of the Periodicity Influencecontrasting
confidence: 98%
“…According to Biswas et al (2017), these defects are originated by impurities present in the deposition chamber such as dust and flakes from the walls. Furthermore, they proved that the amount of the area occupied by defects is influenced by changing the pressure (BISWAS et al, 2018a) and bias (BISWAS et al, 2018b). Results from periodicity evaluation can be found in Table 18.…”
Section: Fourth Stage -Evaluation Of the Periodicity Influencementioning
confidence: 92%
See 1 more Smart Citation
“…It was demonstrated by [8,31], and [36] that for coatings prepared by DGLAD, the properties were In both Al-containing coatings, it was possible to see round morphological defects of a few microns distributed along the surface. These defects are inherent in the sputtering process and unavoidable to some level [33,34]. We observed that CrN presented finer grains and the addition of Al increased grain size.…”
Section: Coating Morphologymentioning
confidence: 62%